The Value of Supporting Education Research in the Academic Environment: The Hospital for Special Surgery Academy of Rheumatology Medical Educators. (July 2021) - Berman, Jessica R.; Aizer, Juliet; Tiongson, Michael D.; Bass, Anne R.; Parrish, Edward J.; Robbins, Laura; Paget, Stephen A.
Abstract : Problem: Medical education academies have been instrumental in providing greater recognition of and promotion for clinician–educators. However, producing education scholarship is essential for clinician–scholar–educator career advancement. Grant funding for education research and protected time to produce scholarship are still lacking for interested physicians, in part due to institutional budget constraints and competing priorities. Approach: The Hospital for Special Surgery Academy of Rheumatology Medical Educators was founded in 2011 to promote education scholarship through grants awarded to educators interested in research. Educators were asked to submit proposals aimed at the development of new teaching programs and curricular change. Selected applicants received up to 50, 000 per year for one year. Grant money was obtained through directed fundraising from donors. Information from annual grant updates and survey responses from grant recipients in 2017 were used to assess the academy's effectiveness. Outcomes: Since 2012, 32 grants have been awarded, totaling 954, 045 in funding. Recipients have produced national meeting abstracts, posters, oral presentations, and manuscripts and created unique curricula and electronic learning tools for medical students, residents, fellows, faculty, and patients. Four educators with demonstrated interest and research outcomes were identified during the pilot and received additional funding and support from a dedicated education research assistant. Next Steps: The academy and the innovations grants program highlight the talents of under-supported and under-recognized teaching faculty by allowing them to distinguish themselves academically as clinician–scholar–educators. The success of these educators emphasizes the clear advantages of a formalized structure to achieve the hospital's education goals. Next steps include providing support for a rheumatology fellow to develop an education research career rather than one in bench, clinical, or translational research. Abstract : Supplemental Digital Content is available in the text.